Left ventricular structure and function following renal sympathetic denervation in patients with HFpEF: an echocardiographic 9-year long-term follow-up - Vogt, Alexander; Plehn, Alexander; Atti, Carlo; Nussbaum, Michael; Tongers, Jörn; Sedding, Daniel; Dutzmann, Jochen (Frontiers in Cardiovascular Medicine, 2024)
Background: High blood pressure is a major risk factor for cardiac remodeling and left ventricular hypertrophy, increasing cardiovascular risk and leading to heart failure with preserved ejection fraction (HFpEF). Since renal sympathetic denervation (RDN) reduces blood pressure in the long term, we wanted to investigate the long-term effect of RDN in patients with HFpEF in the present analysis. Methods: Patients previously enrolled in a local RDN registry who underwent high-frequency RDN with the Symplicity Flex® renal denervation system between 2011 and 2014 were followed up. The patients were assessed by 24-hour ambulatory blood pressure measurement, transthoracic echocardiography and laboratory tests. We used the echocardiographic and biomarker criteria of the HFA-PEFF Score to identify patients with HFpEF. Results: Echocardiographic assessment was available for 70 patients at 9 year long-term follow-up. 21 of these had HFpEF according to the HFA-PEFF Score. We found a significant reduction of the HFA-PEFF Score from 5.48±0.51 points at baseline to 4.33±1.53 points at 9 year follow-up (P<0.01). This decrease was due to a reduction rather in morphologic and biomarker subcategories [from 1.95±0.22 to 1.43±0.51 points (P<0.01) and from 1.52±0.52 to 0.90±0.63 points (P<0.01), respectively] than functional. Morphologically, left ventricular hypertrophy and left atrial dilation were reduced. Conclusions: The present analysis suggests that RDN may lead to a regression of the extent of HFpEF beyond the reduction in blood pressure and thus possibly contribute to an improvement in prognosis. More detailed information will be provided by ongoing randomized sham-controlled trials.